(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
The United Nations have developed the 2030 Agenda for Sustainable Development as a global agreement aiming to eradicate extreme poverty, fight inequality and injustice and leave no one behind. Agreed by world leaders at the UN in 2015, the 17 Sustainable Development Goals (SDGs) succeed the well-known Millennium Development Goals (MDGs). Parts of the Goals directly address environmental issues. Other do indirectly. In response to this growing awareness, the European Union has enacted a number of policies targeting environmental issues, including lowering carbon emissions and water conservation. It can be argued that the EU is at the forefront of addressing the environmental issues outlined in the SDGs. These policies are mentioned in this Paper and they are to be considered strategic. Artificial Intelligence has been having an impact in human activities for decades. Lately the impact is happening exponentially. The European Union is aware of such a fact and it implements policies towards increasing innovation in the public and private sector, including funding programmes and instruments to foster business development and efficiency in the Union and in the Member States. AI is also capable of having a profound impact in the environmental issues that the Agenda 2030 is bringing.